Les raids vikings dans l’historiographie saxonne : une peur héréditaire - Frey, Christian (Presses universitaires de Rennes, 2019)
Viking raids are an important part of Saxon historiography. The northern neighbours not only fought wars on the frontier, but also travelled the rivers with their ships to raid cities such as Hamburg. The reporters of Saxon history treated the experience of those attacks and narrated the stories of the fights, using narrative patterns inherited from Frankish examples. In addition, the Vikings performed certain tasks in the Saxon texts. They served as foreshadowers of bad events, accompanied bad times, and were part of the perceived Christian salvific history. This article examines the basic lines of the tradition of narrating Viking encounters–from the first contacts in England and France to the Saxon historians like Helmold of Bosau and Adam of Bremen. Constitutive for the Saxon reports was the perceived cultural and religious difference from the Scandinavians. Keeping all these in mind, a reinterpretation of medieval texts becomes possible–and the research on Viking history can be enriched with the history of contemporary perception.